VD_FINDINFO HC / 2013 / 696 vom 28. August 2013 - VD Tribunal cantonal (2013)
SOCIÉTÉ SIMPLE, CONCUBINAGE, HOMOSEXUALITÉ, LIQUIDATIONEN GÉNÉRAL, PARTAGESENS GÉNÉRAL | 530 CO, 567 CPC, 596 CPC, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 316 al. 1 CPC (CH)